Chondroblastic osteosarcoma of the maxilla: diagnostic challenges on incisional biopsy and report of a case - Gimenez, Lara Cristina Oliver; Sedassari, Bruno Tavares; Nagano, Cibele Pidorodeski; Rocha, André Caroli; Sousa, Suzana Cantanhede Orsini Machado de; Pinto-Júnior, Décio dos Santos (Journal of Oral Diagnosis, 2018)
Osteosarcoma is a rare mesenchymal neoplasm characterized by osteoid production. Its neoplastic cells can synthesize variable kinds of matrix which determines the sub types as the chondroblastic variant and its cartilaginous matrix. We report a case of a 30-year- old man who presented a painful swelling in the right posterior maxilla, associated to teeth mobility. Radiographic exam showed bone rarefaction with poorly defined margins and root resorption in the corresponding area. An incisional biopsy was performed and histopathologic examination revealed proliferation of mesenchymal spindle-shaped cells in a stroma with irregular, immature and basophilic cartilaginous tissue without osteoid tissue. The cell were diffusely positive for S100 protein. A provisional diagnosis of chondrosarcoma was rendered until the excisional biopsy revealed the presence of osteoid tissue possibiliting a final diagnosis of chondroblastic osteosarcoma. Differentiating between chondrosarcoma and chondroblastic osteosarcoma in incisional biopsies may be a hard task when material is scarce, often incurring in the need for further biopsy. Correct diagnosis is essential for the correct treatment.